Finger Painting sebagai upaya pengenalan warna dan pengembangan motorik halus pada anak PAUD Mantriwirya Surabaya - Galuh Kartika Dewi; Anggralita Sandra Dewi; Eni Nurhayati; Ery Rahmawati (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2021)
Abstract The age of 3-6 years is a sensitive period or sensitive period in children, namely a period where a certain function needs to be stimulated, directed so that its development is not hampered. The right stimulus in children during their growth period certainly has a very good impact on their development. At this stage the development of both cognitive, emotional, language, and sensory. In each of these developments, each development has an important role in each of its aspects. Fine motor development can be identified through drawing and cutting activities. The results of drawing in children with fine motor skills are able to draw simple pictures and are able to recognize colors. The problem for PAUD Mantriwirya children is the lack of fine motor development in children due to the lack of direct and visual activities. As a form of increasing children's creativity during their growth period, it is necessary to do various appropriate stimuli, finger painting is one way to hone children's fine motor skills and color recognition. The benefits that can be taken from efforts to improve children's fine motor skills through finger painting activities are for children who are involved as research subjects that have direct implications for changes and improve children's fine motor skills, To increase creativity and new ideas in creating an atmosphere and atmosphere. interest in children's learning, as a means to increase the form of activities in PAUD Mantriwirya. Keywords: Finger Painting, Color recognition, Fine motoric, PAUD